The Impact of Premature Childbirth on Parental Bonding - Hannah N. Hoffenkamp; Anneke Tooten; Ruby A.S. Hall; Marcel A. Croon; Johan Braeken; Frans Willem Winkel; Ad J.J.M. Vingerhoets; Hedwig J.A. van Bakel (Evolutionary Psychology, 2012)
The development of an affectionate parent-infant bond is essential for a newborn infant's survival and development. However, from evolutionary theory it can be derived that parental bonding is not an automatic process, but dependent on infants' cues to reproductive potential and parents' access to resources. The purpose of the present study was to examine the process of bonding in a sample of Dutch mothers ( n = 200) and fathers ( n = 193) of full-term ( n = 69), moderately premature ( n = 68), and very premature infants ( n = 63). During the first month postpartum parents completed the Pictorial Representation of Attachment Measure (PRAM) and Postpartum Bonding Questionnaire (PBQ). Longitudinal analyses revealed that mothers' PRAM scores decreased after moderately preterm delivery, whereas decreases in PRAM scores occurred in both parents after very preterm delivery. As lower PRAM scores represent stronger feelings of parent-infant connectedness, our findings suggest a higher degree of bonding after premature childbirth. Results of the PBQ analysis were in line with PRAM outcomes, as parents of preterm infants reported less bonding problems compared to parents of full-terms. These findings support the hypothesis that in affluent countries with adequate resources, bonding in parents of preterm infants on average may be higher than in parents of full-term infants.